Mechanism of bacterial gene rearrangement: SprA-catalyzed precise DNA recombination and its directionality control by SprB ensure the gene rearrangement and stable expression of spsM during sporulation in Bacillus subtilis. Issue 11 (23rd May 2017) - Abe, Kimihiro; Takamatsu, Takuo; Sato, Tsutomu
Abstract: A sporulation-specific gene, spsM, is disrupted by an active prophage, SPβ, in the genome of Bacillus subtilis . SPβ excision is required for two critical steps: the onset of the phage lytic cycle and the reconstitution of the spsM -coding frame during sporulation. Our in vitro study demonstrated that SprA, a serine-type integrase, catalyzed integration and excision reactions between attP of SPβ and attB within spsM, while SprB, a recombination directionality factor, was necessary only for the excision between attL and attR in the SPβ lysogenic chromosome. DNA recombination occurred at the center of the short inverted repeat motif in the unique conserved 16 bp sequence among the att sites (5΄-ACAG AT AA/A GCTGT AT-3΄; slash, breakpoint; underlines, inverted repeat), where SprA produced the 3΄-overhanging AA and TT dinucleotides for rejoining the DNA ends through base-pairing. Electrophoretic mobility shift assay showed that SprB promoted synapsis of SprA subunits bound to the two target sites during excision but impaired it during integration. In vivo data demonstrated that sprB expression that lasts until the late stage of sporulation is crucial for stable expression of reconstituted spsM without reintegration of the SPβ prophage. These results present a deeper understanding of the mechanism of the prophage-mediated bacterial gene regulatory system.